Associations between body mass index trajectories in childhood and cardiovascular risk factors in adulthood. (December 2020) - Blond, Kim; Aarestrup, Julie; Vistisen, Dorte; Bjerregaard, Lise G.; Jensen, Gorm Boje; Petersen, Janne; Nordestgaard, Børge G.; Jørgensen, Marit E.; Jensen, Britt Wang; Baker, Jennifer L.
Abstract: Background and aims: Children with a growth trajectory of overweight have higher levels of cardiovascular disease (CVD) risk factors than children with a normal-weight trajectory. However, less is known about how trajectories of body mass index (BMI) across the rest of the BMI spectrum relate to CVD risk factors and whether adult BMI affects these associations. Our aim was to examine associations between childhood BMI trajectories and adult CVD risk factors. Methods: We included 2466 individuals with childhood weights and heights (ages 6–14) from the Copenhagen School Health Records Register and adult CVD risk factors (ages 20–81) from the Copenhagen City Heart Study. Associations between childhood BMI trajectories identified by latent class modelling and CVD risk factors were examined using generalized linear regression analyses with and without adjustment for adult BMI. Normal-weight and overweight were defined by growth references from the Centers for Disease Control and Prevention. Results: We identified four childhood trajectories within the normal-weight spectrum and one trajectory of overweight. Compared to the trajectory with the lowest BMI level, several higher BMI trajectories were associated with worse circumference, HDL and glucose homeostasis in adulthood. The highest trajectory was additionally associated with higher total cholesterol and triglycerides. When adjusting for adult BMI, the higher BMI trajectories had lower waist circumference, blood pressure and triglycerides. Conclusions: Trajectories of BMI within the normal-weight range and in the overweight range are associated with a worse CVD risk profile than in the lowest BMI trajectory, and these associations are modifiable by growth after childhood. Graphical abstract: Image 1 Highlights: Five different trajectories of body mass index from ages 6-14 were identified in a population of 2466 Danish children. The trajectory above overweight cutoffs was associated with the worst cardiovascular disease risk factor profile. Even trajectories below overweight cutoffs had worse cardiovascular disease risk factor profiles than the lowest trajectory. These associations appeared to be modifiable by body mass index development after age 14.